Mixed convection boundary layer flow past a horizontal circular cylinder in viscoelastic nanofluid with constant wall temperature - Rahimah, Mahat; Noraihan Afiqah, Rawi; Abdul Rahman, Mohd Kasim; Sharidan, Shafie (Penerbit UTM Press, 2017)
The steady of two-dimensional convection boundary layer flow of viscoelastic nanofluid over a circular cylinder with constant wall temperature is investigated in this paper. Carboxymethyl cellulose solution-water (CMC-water) is chosen as the base fluid and copper as a nanoparticle with the Prandtl number Pr = 6.2. The governing boundary layer partial differential equations are transformed into dimensionless forms. Then the obtained equations are solved numerically by using the Keller-Box method. This paper focus on the effect of selected parameter on the flow and heat transfer characteristics and be presented in graphs. The results show that, the velocity profiles are increased while the temperature profiles are decreased by increasing the values of nanoparticles volume fraction and viscoelastic parameter, respectively. Also, the values of reduced skin friction are increased by increasing mixed convection parameter, but the values of heat transfer coefficient produce an opposite behavior with an increasing in mixed convection parameter.